Continuous white-blue LED light exposition delays postharvest senescence of broccoli - Hasperué, Héctor Joaquín (2016)
In this work, the impact of low intensity (20 μmol m-2 s-1) continue illumination with white and blue light-emitting diodes (WB LED) on the shelf life of broccoli heads stored at 5 °C or at 22 °C was assessed. At both temperatures, heads stored under WB LED showed the highest levels of chlorophylls, reflected in a higher Hue angle and lower L* values compared to controls stored in the darkness. Also, during storage at 22 °C the treated samples had a slower rate of sugar lost compared to dark stored controls. At 5 °C, glucose and fructose levels were maintained and sucrose was increased by the WB LED treatment. The dark stored controls showed the highest accumulation of antioxidant compounds, but there were no differences in ascorbic acid content except for the last storage day at 5 °C, being the WB LED samples which had a slightly higher level (p < 0.05). Finally, treated samples showed an increment in the total carotenoid content, mainly during storage at 22 °C. According to the results, WB LED treatment would be a feasible and low cost technology to enlarge the postharvest storage of whole broccoli heads.